2010
DOI: 10.1097/mao.0b013e3181e8f36c
|View full text |Cite
|
Sign up to set email alerts
|

New Considerations in the Cause of Spontaneous Cerebrospinal Fluid Otorrhea

Abstract: Patients with spontaneous cerebrospinal fluid otorrhea are often middle-aged and obese, with females being affected nearly twice as often as males. Empty or partially empty sella was observed in 80% of patients with spontaneous cerebrospinal fluid otorrhea as demonstrated by preoperative magnetic resonance imaging. Patients with spontaneous cerebrospinal fluid otorrhea who display these demographic and radiographic features should be further evaluated for the presence of idiopathic intracranial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 28 publications
7
90
2
1
Order By: Relevance
“…8,22,24,26,27 We found that the mean BMI and the prevalence of empty sella syndrome were higher in patients with spontaneous lesions than in those with nonspontaneous lesions; however, these differences did not reach statistical significance. Our data reveal a female preponderance among patients with spontaneous CSFFs, similar to that observed among patients with idiopathic intracranial hypertension syndrome.…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…8,22,24,26,27 We found that the mean BMI and the prevalence of empty sella syndrome were higher in patients with spontaneous lesions than in those with nonspontaneous lesions; however, these differences did not reach statistical significance. Our data reveal a female preponderance among patients with spontaneous CSFFs, similar to that observed among patients with idiopathic intracranial hypertension syndrome.…”
mentioning
confidence: 43%
“…It has been hypothesized that elevated intracranial pressure may contribute to progression of temporal bone encephaloceles and CSFF, and an increased risk of recurrence following repair. 1,8,22,26 Given the rarity of the studied conditions, few large series exist in the literature, and optimal surgical management remains controversial. 7,14,15,20,21 Treatment options include the transmastoid approach with tegmen repair or tympanomastoid obliteration, subtemporal middle fossa craniotomy, or a combined mastoid-middle fossa approach.…”
mentioning
confidence: 99%
“…1 Recently there has been growing evidence that obesity is also a risk factor for development of spontaneous temporal bone CSF leaks. 6,12,17,21 In contrast, little has been written regarding the possible association between obesity and the occurrence of a CSF leak following VS surgery. 8,14 Diaz Anadon et al studied 170 patients who had undergone surgery for tumors in the cerebellopontine angle (163 of whom had a VS) and found no relationship between CSF leaks and BMI.…”
Section: Discussion Elevated Bmi As a Risk Factor For A Csf Leakmentioning
confidence: 99%
“…14 The purpose of the present study is to add our series to the limited number of previously published cases, to compare the PF variety of transtemporal CSF leakage with the more common MF route in terms of demographics, clinical presentation, imaging characteristics, and potential etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…The MF is more prone to dehiscence and CSF leak due to a combination of a thinner bony plate and a higher proportion of AGs compared with the posterior petrous face. [11][12][13] Recently in the last 5 to 10 years, associations between temporal bone CSF leak, obesity, [6][7][8]14,15 and idiopathic intracranial hypertension (IIH) 3,5,6,[14][15][16] have been noted. IIH interestingly shares the similar demographics of age 40 to 60, female gender, and BMI greater than 30.…”
mentioning
confidence: 99%